Nexus between stock returns, funding liquidity and COVID-19 - Godfrey Marozva; Margaret Rutendo Magwedere (SPOUDAI - Journal of Economics and Business, 2021)
Using a panel of stock indices of the BRICS countries from 31 December 2019 to 17 October 2020, the nexus between funding liquidity, stock returns and COVID-19 pandemic is examined using the fixed effects model. Results show that funding liquidity and the COVID-19 pandemic interacts positively with stock market returns. The findings were irrational to the theoretical predictions as stock markets seem to be recovering from their initial losses despite the spike in the number of COVID-19 cases. In the early periods, investors appeared to have exaggerated the lethality of the virus but now they have become used, resilient, and optimistic despite a surge in the number of reported new cases and deaths. The findings also confirmed the fact that stock markets respond to macroeconomic effects with a lag. Therefore, the ongoing policy interventions and individual behaviour are achieving the desired goal of stabilizing the situation. Thus, emerging markets governments were proactive and pragmatic in dealing with the pandemic as the effects of adopted economic policies outweighed/ thwarted the negative impact of the witnessed spike in COVID-19 cases. The revelation that funding liquidity contrary to theory improved as the pandemic worsened indicates a fruitful area for future research.
Keywords: G10; G12; C23; 330; funding liquidity; COVID-19; stock market returns; volume